2016
DOI: 10.1007/s00198-016-3662-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body electromyostimulation to fight sarcopenic obesity in community-dwelling older women at risk. Resultsof the randomized controlled FORMOsA-sarcopenic obesity study

Abstract: WB-EMS is a safe and attractive method for increasing muscle mass and functional capacity in this cohort of women 70+ with SO; however, the effect on body fat is minor. Protein-enriched supplements did not increase effects of WB-EMS alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(183 citation statements)
references
References 38 publications
4
177
1
1
Order By: Relevance
“…Revisiting the primary hypothesis of the study, the fact that despite comparable high and significant effects on muscle mass in both WB-EMS groups, Kemmler et al33 suggested that the mechanism of WB-EMS effects on cardiometabolic risk factors may not be necessarily muscle-induced. Indeed, the traditional belief of a generally beneficial effect of muscle tissue on cardiometabolic risk34 is vague.…”
Section: Discussionmentioning
confidence: 95%
“…Revisiting the primary hypothesis of the study, the fact that despite comparable high and significant effects on muscle mass in both WB-EMS groups, Kemmler et al33 suggested that the mechanism of WB-EMS effects on cardiometabolic risk factors may not be necessarily muscle-induced. Indeed, the traditional belief of a generally beneficial effect of muscle tissue on cardiometabolic risk34 is vague.…”
Section: Discussionmentioning
confidence: 95%
“…However, our recent studies determined that drawing lots and thus randomizing “oneself” boosted acceptance of a nonfavored study group, a very important aspect in nonblindable intervention studies [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 studies have investigated its influence on physical fitness and health in trained and untrained individuals, and in patients who cannot perform conventional modalities of exercise because of physical or mental illness . Most of these studies (n = 10) have examined the role of whole‐body electromyostimulation training on body composition parameters, showing that this training modality induced a generally decrease of FM and a generally increase of LM in (a) sedentary older men and women with sarcopenic obesity (all of them aged > 70 years old), (b) in sedentary older women with obesity (aged > 70 years old), (c) in moderately trained male runners, (d) in sedentary healthy men (aged 30‐50 years old), and (e) in moderately trained healthy women (aged > 55 years old) . In addition, a study conducted in sedentary older women with osteopenia (aged > 70 years old) suggested that a 54‐week whole‐body electromyostimulation training program could be an option for maintaining BMD …”
Section: Introductionmentioning
confidence: 99%